New approach to water users’ associations in pump-based irrigation schemes in Myanmar results in equitable water allocation and boosts production - CGIAR Research Program on Water, Land and Ecosystems (2020)
Funded through the Livelihoods and Food Security Fund (LIFT) from December 2016 to mid-2019, WLE/IWMI developed a novel approach to establishing water users? associations (WUAs) in pump-based irrigation schemes in Myanmar. This was accompanied by the introduction of new crop varieties and high-quality pulse and rice seeds by Welthungerhilfe and ICRISAT. Despite a drought, farmers reported 1.5 years after LIFT ended that their WUA had enabled them to double the irrigated area and increase crop production.